DIGITALISASI PRAKTIK JURNALISTIK DI ERA NEW NORMAL: Studi Kasus pada Jurnalis Media MAL Online - Citra Antasari; Muhammad Isa Yusaputra; Nur Haidar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Media Alkhairat Palu newspaper's decision to change its performance on online media platforms has fundamental considerations. One of them is part of self-adaptation to the impact of the Covid-19 pandemic which has taken place in the last two years. Apart from management, the work patterns and skills of media workers, especially journalists, are one that demands change for the better. Three basic things that are the goal of this research are to look at, First, related to the expertise in using software and social media (cognitive dimension). Second, journalists' views on the potential use of internet technology in news production (evaluative dimension). Third, the emergence of new practices that are adapted in the network model of making news (performative dimension). This research was carried out for approximately two months, at the Media Alkhairat Palu office. Using two informants as research subjects selected using purposive sampling method. Based on the research results, it was found that Alkhairat Media made a number of adaptations in the digital transformation process that was carried out. From a cognitive aspect, most journalists are quite qualified in using software or a number of social media. From the evaluative aspect, it was found that when transformed into an online media, internet technology became the most important part in the process of making news and its production. Then from the performative aspect, what stands out from the process of digitizing online media is the process of gathering news and changes in editorial work patterns.